2023
DOI: 10.7861/clinmed.2023-0078
|View full text |Cite
|
Sign up to set email alerts
|

Early applications of ChatGPT in medical practice, education and research

Abstract: ChatGPT, which can automatically generate written responses to queries using internet sources, soon went viral after its release at the end of 2022. The performance of ChatGPT on medical exams shows results near the passing threshold, making it comparable to third-year medical students. It can also write academic abstracts or reviews at an acceptable level. However, it is not clear how ChatGPT deals with harmful content, misinformation or plagiarism; therefore, authors using ChatGPT professionally for academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 13 publications
1
19
0
Order By: Relevance
“…Building on the proposal to integrate AI into medical programs to prepare students for their future use of such tools in professional contexts [ 5 , 8 , 28 , 29 ], the implementation of ChatGPT has emerged as a potentially transformative force in medical education [ 30 , 31 ], offering support to students in their learning journey [ 30 , 32 ]. The questionnaire administered to medical faculty students provided valuable insights into their perspectives and experiences with ChatGPT, shedding light on their attitudes, preferences, and intentions regarding the incorporation of AI chatbots in educational environments.…”
Section: Discussionmentioning
confidence: 99%
“…Building on the proposal to integrate AI into medical programs to prepare students for their future use of such tools in professional contexts [ 5 , 8 , 28 , 29 ], the implementation of ChatGPT has emerged as a potentially transformative force in medical education [ 30 , 31 ], offering support to students in their learning journey [ 30 , 32 ]. The questionnaire administered to medical faculty students provided valuable insights into their perspectives and experiences with ChatGPT, shedding light on their attitudes, preferences, and intentions regarding the incorporation of AI chatbots in educational environments.…”
Section: Discussionmentioning
confidence: 99%
“…Mehta et al (2021) who measured perception of medical students about the role of AI, reports that the most students think that AI will take over jobs in terms of providing medical documentation, planning, and resource management, but did not see that AI could replace doctors. Sedaghat (2023) reported that the performance of ChatGPT to pass a medical exam is at an acceptable level and it has capability to change medical practices. A study by Friederichs et al (2023) reported that ChatGPT outperformed almost all medical students in first, second, and third years in the German State exam in Progress Test Medicine.…”
Section: Medical Students' Use Of Ai/chatgptmentioning
confidence: 99%
“…One remarkable application of AI in this realm is the development of large language models, such as ChatGPT, which have gained significant attention for their ability to generate human-like text based on prompts. ChatGPT’s versatile capabilities hold promise for reshaping medical practices, enhancing patient care, and revolutionising the way healthcare professionals interact with both patients and data [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%